The postbinding activity of scavenger receptor class B type I mediates initiation of hepatitis C virus infection and viral dissemination1. Issue 2 (28th December 2012) - Zahid, Muhammad N.; Turek, Marine; Xiao, Fei; Dao Thi, Viet Loan; Guérin, Maryse; Fofana, Isabel; Bachellier, Philippe; Thompson, John; Delang, Leen; Neyts, Johan; Bankwitz, Dorothea; Pietschmann, Thomas; et al.
Abstract Scavenger receptor class B type I (SR‐BI) is a high‐density lipoprotein (HDL) receptor highly expressed in the liver and modulating HDL metabolism. Hepatitis C virus (HCV) is able to directly interact with SR‐BI and requires this receptor to efficiently enter into hepatocytes to establish productive infection. A complex interplay between lipoproteins, SR‐BI and HCV envelope glycoproteins has been reported to take place during this process. SR‐BI has been demonstrated to act during binding and postbinding steps of HCV entry. Although the SR‐BI determinants involved in HCV binding have been partially characterized, the postbinding function of SR‐BI remains largely unknown. To uncover the mechanistic role of SR‐BI in viral initiation and dissemination, we generated a novel class of anti–SR‐BI monoclonal antibodies that interfere with postbinding steps during the HCV entry process without interfering with HCV particle binding to the target cell surface. Using the novel class of antibodies and cell lines expressing murine and human SR‐BI, we demonstrate that the postbinding function of SR‐BI is of key impact for both initiation of HCV infection and viral dissemination. Interestingly, this postbinding function of SR‐BI appears to be unrelated to HDL interaction but to be directly linked to its lipid transfer function. Conclusion: Taken together, our results uncover a crucial role of the SR‐BI postbinding function for initiation and maintenance of viral HCV infection that does not require receptor‐E2/HDL interactions. The dissection of the molecular mechanisms of SR‐BI–mediated HCV entry opens a novel perspective for the design of entry inhibitors interfering specifically with the proviral function of SR‐BI. (HEPATOLOGY 2013)